A review of natural fiber-based filaments for 3D Printing: filament fabrication and characterization - Ahmad, Mohd Nazri; Ishak, Mohamad Ridzwan; Mohammad Taha, Mastura; Mustapha, Faizal; Leman, Zulkiflle (Multidisciplinary Digital Publishing Institute, 2023)
Today, additive manufacturing (AM) is the most recent technology used to produce detailed and complexly built parts for a variety of applications. The most emphasis has been given to fused deposition modeling (FDM) in the development and manufacturing fields. Natural fibers have received attention in the area of 3D printing to be employed as bio-filters with thermoplastics, which have prompted an effort for more ecologically acceptable methods of manufacturing. The development of natural fiber composite filaments for FDM requires meticulous methods and indepth knowledge of the properties of natural fibers and their matrices. Thus, this paper reviews natural fiber-based 3D printing filaments. It covers the fabrication method and characterization of thermoplastic materials blended with natural fiber-produced wire filament. The characterization of wire filament includes the mechanical properties, dimension stability, morphological study, and surface quality. There is also a discussion of the difficulties in developing a natural fiber composite filament. Last but not least, the prospects of natural fiber-based filaments for FDM 3D printing are also discussed. It is hoped that, after reading this article, readers will have enough knowledge regarding how natural fiber composite filament for FDM is created.